Neonatal Outcome Among Adolescent and Adult Pregnancy in a Tertiary Care Center of Nepal - Adhikari, Jyoti; Kharel, Shristi; Bahl, Lalita; Poudel, Deepal; K.C., Rajesh (Journal of Nepalgunj Medical College, 2018)
Background: Teenage pregnancy is a common public health problem worldwide which is detrimental to the health of mother and child and has long been considered a high-risk situation. The risk of low birth weight (LBW) and preterm delivery is particularly high among teenagers. Methods: A comparative study was conducted in Nepalgunj Medical College Teaching Hospital, Kohalpur during the period of July 2015 to June 2016. The study was carried out to compare the immediate neonatal outcome and morbidity pattern in neonates of 50 adolescent and 50 adult mothers. Results: In the present study, 84% belonged to adolescent mother group (17-19 years) whereas 50% belonged to adult mother group (20-23 years). Illiteracy was seen more in adolescent mothers (62%) and most were from rural areas (68%). The common immediate neonatal outcome found in adolescent and adult mothers were preterm delivery (96% vs. 52%; p value 0.001), low birth weight (LBW) (70% vs. 38%; p value 0.001). The common neonatal morbidities seen significantly high in neonates of adolescent mothers, viz: Neonatal sepsis (NNS)(54% vs. 20% p value <0.02), apnea (30% vs. 14% P value <0.02), neonatal jaundice(NNJ)(44% vs. 30% p value <0.01) while the other morbidities found were birth asphyxia (20% vs. 14%; p value <0.1), Respiratory distress syndrome (RDS) (36% vs. 24% p value<0.1), anemia (16% vs. 8%; p value <0.1), seizure (10% vs. 8%; p value <0.1), meconium aspiration syndrome (MAS) (6% vs. 18%; p value<0.1) and intrauterine growth retardation(IUGR)(22% vs. 20%; p value <0.5). Similarly mortality was found to be more in neonates of adolescent mothers (14% vs. 8%; p value <0.1). Conclusion: Adolescent pregnant mothers are at risk of having poor neonatal outcome and morbidities like NNS, NNJ, RDS, apnea, IUGR, birth asphyxia, anemia and seizure. JNGMC, Vol. 14 No. 2 December 2016, Page: 56-59